Multi-modal interactions on urban streets: New conflicts and emerging challenges in a mixed-use neighborhood: A case study of New York. (September 2021) - Conway, Moira; Conway, Alison
Abstract: New York, like many US cities has recently seen gentrification in previously industrial dominated neighborhoods. As a result, urban streets in the affected neighborhoods must now accommodate a range of street uses, including walking, cycling, and commercial vehicle trips. Through mapping, spatial analysis, and development of collision frequency models in two case study areas located in the Brooklyn and Queens Boroughs of New York City, this project aims to identify the built environment factors that affect collision frequencies and to understand if gentrification has any significant effect on local street safety. Results of this project can inform policy and planning decisions for street design, land use decisions, traffic control, and curb management decisions. Highlights: Identify factors influencing the frequency of multi-modal traffic conflicts in gentrifying, mixed use areas of New York City. Model factors that affect collision frequencies using GIS, spatial analysis, and poisson regression. Explanatory variables examined in the model include land use characteristics, infrastructure characteristics, and a gentrification ranking. Commercial vehicle; non-motorized collisions cluster near residences. All types of collisions are more frequent on truck routes. Bicycle facility and gentrification impacts vary by neighborhood.